Peirce, abducción y práctica médica (2001)
This paper presents an alternative view for understanding abduction as "inference to the best explanation", than can account from the simplest perception to the introduction of any new ideas. Subsequently the view offered is applied to medical practice and some consequences are extracted for it. The discussion is considered in the context of Peirce's theories of men classification, fixation of belief and inquiry.